Thirty years of design for sustainability: an evolution of research, policy and practice. (9th February 2021) - Bhamra, Tracy; Hernandez, Ricardo J.
Abstract: This paper builds on the lead author's keynote address to the Design Society's 22nd International Conference on Engineering Design in 2019, and in doing so provides a personal perspective on the development of the field of design for sustainability. It begins by describing some of the history of the research from the late 1980s until the present day. This is followed by an analysis of the way in which design for sustainability has been reflected within the International Conference on Engineering Design over the last 30 years, highlighting the way in which the focus has shifted over this time from a focus on recycling and end of life to today where sustainability is playing a leading role in the research. The analysis compares the evolution of the subject with the wider policy and practice perspectives linked to global recognition of the need to move towards Sustainable Development. Finally, the paper reflects on the lessons to be learned from this work and their implications for design research illustrating that engineering design has an opportunity to take more leadership within design for sustainability research and use this to enable change within industry.